Failing to meet the goals of periodontal recall programs. What next?. Issue 1 (31st July 2017) - McCracken, Giles; Asuni, Abisola; Ritchie, Mark; Vernazza, Christopher; Heasman, Peter
Abstract: Supportive periodontal care is a crucial aspect of the management of chronic periodontitis and peri‐implantitis and is inevitably a long‐term commitment for both the clinician and the patient. The principal goals of supportive care are to achieve a high standard of plaque control, minimize bleeding and maintain pockets at less than 6 mm. Gain of attachment around natural teeth during supportive periodontal care has been reported, although gain of attachment and of bone during supportive care may be a more pragmatic and aspirational aim in the longer term. Furthermore, we occasionally see patients for whom, despite excellent home and professional care (surgical or nonsurgical), including the management of risk factors, supportive periodontal care appears to be failing and therefore for such patients the clinician needs to consider further management options. This review considers, in particular, the options of using local or systemically delivered antimicrobials to eradicate periodontal and peri‐implant disease progression and discusses the extent to which culture and sensitivity testing before the prescription of systemically delivered antimicrobials may be a cost‐effective alternative to prescribing 'blind'.